2000
DOI: 10.1034/j.1600-0579.2000.040303.x
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perceptions of seminar and lecture‐based teaching in restorative dentistry

Abstract: In an era of self-directed learning, it is important to seek the views of dental students regarding their learning experience. Using an anonymous questionnaire, clinical dental students' perceptions of seminar and lecture-based teaching in restorative dentistry were sought. 116 of 136 questionnaires circulated were returned for analysis giving a response rate of 85%. Clinical seminars as opposed to lectures were, in the opinion of the students, a more effective way of learning, more relevant to self-developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 9 publications
(5 reference statements)
1
24
0
Order By: Relevance
“…[4][5][6][7] There is a need to develop certain strategies to make them interesting. Study by Brunton et al [8] in restorative dentistry had shown the popularity of clinical seminars among students. This should be adopted in pharmacology where seminars pertaining to treatment planning of certain diseases can be organized.…”
Section: Discussionmentioning
confidence: 98%
“…[4][5][6][7] There is a need to develop certain strategies to make them interesting. Study by Brunton et al [8] in restorative dentistry had shown the popularity of clinical seminars among students. This should be adopted in pharmacology where seminars pertaining to treatment planning of certain diseases can be organized.…”
Section: Discussionmentioning
confidence: 98%
“…They are increasingly familiar with modern means of information exchange and communication from a young age. Other research evidence indicates that clinical seminars and active group discussions are generally preferred by students compared with traditional didactic lectures (38). It should be noted, however, that a traditional lecture may have other benefits that more modern approaches cannot match.…”
Section: Methods Of Teachingmentioning
confidence: 99%
“…The results of different investigations of medical studies show that the success of the PBL concept largely depends on the motivation and cooperation of the respective student [26-30]. One major advantage of the PBL concept is undoubtedly small group learning [41], [42], because this form of learning enables students perform better in seminars and to identify themselves with the subject matter, which often significantly increases student motivation [19], [43], [44], [45]. …”
Section: Discussionmentioning
confidence: 99%